Pembuatan Profil Digital Desa Labuan Seram Utara Barat Dengan Google Sites - Janeman Sumah; Ulan Ningsih Etwiory; Hennie Tuhuteru; Laipeny Melianus Imasuly; Roberth Ricky Manaha (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
ABSTRACT The rapid development of technology makes the internet a demand for fulfilling current information. Labuan Village is one of the villages located in North West Seram District, Central Maluku Regency, Maluku Province. Labuan Village is a developing village so not many people know it well. With the existence of information technology, it encourages writers to design a Labuan Village Profile Website with Google Site Services which aims to make the wider community more familiar with it through internet media. With the construction of the Labuan Village Profile Website, it is hoped that it will be able to provide village information, vision and mission, history, organizational structure, population, and as a medium for promoting information on village potential. This research uses a qualitative approach which is expected to be able to produce an in-depth description of speech, writing, and behavior that can be observed from an individual, group, community, and certain organizations in the context of a certain setting that is studied from a whole, comprehensive, and holistic perspective. (Bogdan and Taylor, 1992). The benefit of this research is that apart from what is stated above, it is hoped that the general public will be able to know more about the potential of Labuan Village and the interest of investors to invest, especially in the tourism sector in Labuan Village.. Keywords : Internet, Google Site, Website, Investor ABSTRAK Perkembangan teknologi yang pesat menjadikan internet sebagai tuntutan untuk pemenuhan informasi saat ini. Desa Labuhan adalah salah satu desa yang terdapat pada Kecamatan Seram Utara Barat, Kabupaten Maluku Tengah, Provinsi Maluku. Desa Labuhan merupakan desa berkembang sehingga belum banyak masyarakat mengenal dengan baik. Dengan adanya teknologi informasi, mendorong penulis untuk merancang Website Profil Desa Labuhan dengan Layanan Google Site yang bertujuan agar masyarakat luas dapat lebih mengenalnya melalui media internet. Dengan dibangunnya Website Profil Desa Labuhan, diharapakan dapat memberikan informasi desa, visi misi, sejarah, struktur organisasi, jumlah penduduk, dan sebagai media promosi informasi potensi desa. Penelitian ini menggunakan pendekatan kualitatif yang diharapkan mampu menghasilkan suatu uraian mendalam tentang ucapan, tulisan, dan tingkah laku yang dapat diamati dari suatu individu, kelompok, masyarakat, dan organisasi tertentu dalam konteks setting tertentu yang dikaji dari sudut pandang yang utuh, komprehensif, dan holistik (Bogdan dan Taylor, 1992). Manfaat dari penelitian ini adalah selain yang tertera diatas, diharapkan masyarakat luas dapat lebih mengetahui potensi Desa Labuhan dan ketertarikan dari pihak investor untuk berinvestasi khususnya pada sektor pariwisata di Desa Labuhan. Kata kunci : Internet, Google Site, Website, Investor